Cannulation method for intradiverticular papilla with long oral protrusion using biopsy forceps for axis alignment. Issue 5 (12th July 2018) - Takenaka, Mamoru; Minaga, Kosuke; Kudo, Masatoshi
Abstract : Watch videos of this article.